Identification of Bacteria which Infected The Garra Rufa Fish Cyprinion Macrostomus at Quarantine Office of Soekarno-Hatta Airport - Mustahal Mustahal; Anik Waqiah (JURNAL PERIKANAN DAN KELAUTAN, 2012)
A study has been carried out to identify the bacteria that infected the garra rufa fish (Cyprinion macrostamus) which have been transported through the Quarantine Office of Soekarno - Hatta Airport. These fishes were among the freshwater commodities which frequently transported throughout various countries, because they were commonly used for decreasing the effect of psoriasis in a feet spa treatment, by feeding the dead cells of feet skin. Therefore, the possibility of spreading the diseases during the treatment must be anticipated. In this study the bacteria samples were taken from the fish skin and then cultured in the laboratory. After purification of the cultures, the bacteria were then tested by a serial microbiological methods to identify the bacteria. The results showed that the Garra rufa fish (Cyprinion macrostomus) observed in this study indicated the presence of bacteria of (+) Motile Aeromonas Septicaemia, and (-) of Motile Aeromonas Septicaemia, which were among the diseases of quarantine fishes. While the Aeromonas hydrophylla was also found out, even though not included as diseases of quarantine fishes. Therefore, they may received the health certificate for fish and fish product for export as well as for therapeutic purposes .Keyword: garra rufa, bacterial identification, bacterial pathogen